Programowanie finansowania komunalnych projektów inwestycyjnych w nowej perspektywie finansowej UE 2014–2020 - Sierak, Jacek (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
According to the new EU financial perspective, a significant portion of funds willbe allocated to fund municipal projects, whose beneficiaries include local governmentunits. In the process of obtaining EU subsidies two elements will have greatimportance: investment projects and financial contribution to the investments.The paper focuses on the conditions of implementation of municipal investmentprojects in the new EU programming perspective, and on principles of projectfinancing and the sources of funding.